Exposing the Unique Connection between Metabolism and Virulence in Staphylococcus aureus. Issue 11 (17th November 2016) - Weiss, Andy; Fleeman, Renee M.; Shaw, Lindsey N.
Abstract : In this issue of Cell Chemical Biology, Choby et al. (2016) use a small molecule inhibitor active against fermenting S. aureus to unravel a unique connection between virulence factor production and central metabolism. In so doing, the authors uncover Fe-S cluster assembly proteins as a novel antibacterial target, and deliver a first-in-class scaffold for optimization against anaerobically growing cells. Abstract : In this issue of Cell Chemical Biology, Choby et al. (2016) use a small molecule inhibitor active against fermenting S. aureus to unravel a unique connection between virulence factor production and central metabolism. In so doing, the authors uncover Fe-S cluster assembly proteins as a novel antibacterial target, and deliver a first-in-class scaffold for optimization against anaerobically growing cells.